2015
DOI: 10.1097/eja.0000000000000250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose–insulin–potassium on hyperlactataemia in patients undergoing valvular heart surgery

Abstract: Clinicaltrials.gov identifier: NCT01825720.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…More than 50 years ago the clinical application of glucose insulin-potassium (GIK) solution was presented in cardiac surgery. 17,18,24,25 The study has found insulin is a key component of GIK protecting the myocardium after cardiac surgery. Previous studies have shown the protective effects of insulin on cardiovascular by anti-apoptotic, anti-inflammatory, anti-oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50 years ago the clinical application of glucose insulin-potassium (GIK) solution was presented in cardiac surgery. 17,18,24,25 The study has found insulin is a key component of GIK protecting the myocardium after cardiac surgery. Previous studies have shown the protective effects of insulin on cardiovascular by anti-apoptotic, anti-inflammatory, anti-oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin regulates glucose levels and has anti-apoptosic and anti-inflammatory effects [14][15][16] ; it has been widely used in clinical treatment of diabetes, metabolic syndrome, and MIRI. [17][18][19] Insulin was reported to inhibit the NLPR3 inflammasome activation 14 and enhance PDHc activity by PDHA1 dephosphorylation. 15 Nevertheless, the contributions and molecular mechanisms of PDHA1 in association with insulin and NLRP3-induced pyroptosis in MIRI are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3,46 Variable degrees of hyperglycemia may explain why GIK demonstrated benefit in some investigations 12,28 but not in others. 29,47,48…”
Section: Discussionmentioning
confidence: 99%